(untitled) (Nigerian Journal of Technology, 2015)
This study evaluates and retimes a pre-timed traffic signal using the current volume of traffic and saturation flow headway. Traffic volume count was collected by stationing technicians at each approach lane to record the flow, composition and direction of vehicles through the intersection for every 15 minutes interval from 6.00am to 6.00pm. Saturation flow headway was obtained by placing a video recording device perpendicular to the stop line of each approach lane and allowed to record during the duration of traffic count. Retiming analysis and evaluation was carried out based on Highway capacity model for designing traffic signal timing parameters. The results obtained show an improvement by a reduction in the number of phases from four to three, a reduction in cycle length from 180 seconds to 120 seconds and an improved level of service from F to C. http://dx.doi.org/10.4314/njt.v35i1.2